2015
DOI: 10.1109/tsp.2015.2437844
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Integration Algorithm for a Maneuvering Target With High-Order Range Migration

Abstract: This paper considers the coherent integration problem for a maneuvering target with complex motions, where the velocity, acceleration and jerk result in respectively the first-order range migration (FRM), second-order range migration (SRM) and third-order range migration (TRM) within the coherent pulse interval. A new coherent integration algorithm based on generalized keystone transform (KT) and secondorder dechirp process is proposed, which employs the third-order KT, six-order KT, second-order KT and fold f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 36 publications
1
77
0
1
Order By: Relevance
“…Figure 3(a) shows the result after the third-order KT, six-order KT and phase term compensation .By figure 3(a), it is observed that the total range migration value is 60 and it is reduced by 3. In theory, the RM change in this step is [4] ΔR ≈ a 1 T 3 + a 0 T 2 + 1 2 v 0 T Δr = 3 , where the Result of RFT range walk value corresponding to the unambiguous velocity is v 0 T /Δr ≈ −2 (minus denotes the direction of range walk opposite to the direction of target motion).Therefore, the simulation result is consistent with the theoretical result and TRM and SRM are eliminated.By the de-chirping method, the estimated acceleration is 409.40m s 2 , the estimated jerk is 271.52m s 3 . After GKT, the integration is realized by RFT.The result of RFT is given by Figure 3(b).It is seen that the target can be detected, where the estimated range is18000m,the estimated velocity is 1450m/s.…”
Section: Simulation Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…Figure 3(a) shows the result after the third-order KT, six-order KT and phase term compensation .By figure 3(a), it is observed that the total range migration value is 60 and it is reduced by 3. In theory, the RM change in this step is [4] ΔR ≈ a 1 T 3 + a 0 T 2 + 1 2 v 0 T Δr = 3 , where the Result of RFT range walk value corresponding to the unambiguous velocity is v 0 T /Δr ≈ −2 (minus denotes the direction of range walk opposite to the direction of target motion).Therefore, the simulation result is consistent with the theoretical result and TRM and SRM are eliminated.By the de-chirping method, the estimated acceleration is 409.40m s 2 , the estimated jerk is 271.52m s 3 . After GKT, the integration is realized by RFT.The result of RFT is given by Figure 3(b).It is seen that the target can be detected, where the estimated range is18000m,the estimated velocity is 1450m/s.…”
Section: Simulation Resultssupporting
confidence: 70%
“…Therefore, the velocity of target can be expressed as [4] v 1 = v 0 + Γv amb (6) Where v amb denotes the blind velocity, which is computed by v amb = P RF ·λ…”
Section: Signal Model For Radar Target and Rm Analysisunclassified
See 3 more Smart Citations